Primary Healthcare Marketing: A Bibliometric Study and Research Agenda - Piotr Rościszewski; Mariusz Stępień; Justyna Berniak-Woźny (SAGE Publishing, 2024)
The evolution of our lives has forced changes to the healthcare system and consequently established healthcare marketing as an essential element of health services, including primary health care (PHC). This article aims to analyze the size, structure, and dynamics of research on primary healthcare marketing to identify the main topics and research trends in this area. The authors conducted a bibliographic analysis based on the methods of performance analysis and scientific mapping. The bibliographical analysis covered 1981 publications selected from the Scopus database and was carried out with the use of the MS Excel and VOSviewer applications. The results were supplemented with an in-depth analysis of 34 publications selected based on bibliographic coupling analysis to determine key research trends and results, which increased the understanding of the research area. The conducted research proves that the issue of marketing in primary health care is rarely addressed by researchers, which translates into very limited research results and little impact on the decision-making process in this area. This research field requires much greater commitment, especially in the areas indicated in the future research agenda recommendations.